The provisions of the bankrupt and the provisions. - Ahmed fanws hummadi (Journal of Madenat Alelem University College, 2017)
That the importance of jurisprudence appear in the growing need for it and attests to the huge number of jurisprudence studies ancient and modern which dealt with various issues and different jurisprudential aspects and the recent trends in jurisprudence studies have become a different direction that the previous books of jurisprudence which included in the pages of all the doors of jurisprudence known , emerged substantive studies that address the aspects of jurisprudence research and study.